Comparison of apoptosis in human primary pulmonary endothelial cells and a brain microvascular endothelial cell line co-cultured with Plasmodium falciparum field isolates - Essone, Jean Claude Biteghe Bi (BMC Infect Dis, 2017)
BACKGROUND: Plasmodium falciparum infection can progress unpredictably to severe forms including respiratory distress and cerebral malaria. The mechanisms underlying the variable natural course of malaria remain elusive. METHODS: The cerebral microvascular endothelial cells-D3 and lung endothelial cells both from human were cultured separately and challenged with P. falciparum field isolates taken directly from malaria patients or 3D7 strain (in vitro maintained culture). The capacity of these P. falciparum isolates to induce endothelial cell apoptosis via cytoadherence or not was then assessed. RESULTS: Overall, 27 P. falciparum isolates were collected from patients with uncomplicated malaria (n = 25) or severe malaria (n = 2). About half the isolates (n = 17) were able to bind brain endothelial cells (12 isolates, 44%) or lung endothelial cells (17 isolates, 63%) or both (12 isolates, 44%). Sixteen (59%) of the 27 isolates were apoptogenic for brain and/or lung endothelial cells. The apoptosis stimulus could be cytoadherence, direct cell-cell contact without cytoadherence, or diffusible soluble factors. While some of the apoptogenic isolates used two stimuli (direct contact with or without cytoadherence, plus soluble factors) to induce apoptosis, others used only one. Among the 16 apoptogenic isolates, eight specifically targeted brain endothelial cells, one lung endothelial cells, and seven both. CONCLUSION: These results indicate that the brain microvascular cell line was more susceptible to apoptosis triggered by P. falciparum than the primary pulmonary endothelial cells and may have relevance to host-parasite interaction.